Wicking behavior and drying capability of functional knitted fabrics - Fangueiro, Raúl (2010)
Liquid transporting and drying rate are two vital factors affecting the physiological comfort of sport garments. In this study, plated knitted fabrics produced with functional fiber yarns in the back of the knit (close to the body), combined with polypropylene or polyester in the face (outer surface) were tested in terms of their wicking behavior and drying rate capacity. Functional knitted fabrics were evaluated by vertical and horizontal wicking tests. The drying capability was assessed by drying rate tests under two different conditions, namely, at 20±2°C and 65±3% relative humidity and, in an oven, at 33±2°C, in order to simulate the human body temperature. The influence of the functional fiber used and that of the ground material, polyester or polypropylene, was analyzed and discussed.